Retinoids in scarless skin regeneration: from molecular mechanisms to therapeutic strategies - Wang, Kang; Yang, Ziting; Ma, Yunqi; Liu, Wenhui; Li, Guangshuai; Xu, Xuewen; Li, Qingfeng (Frontiers in Cell and Developmental Biology, 2025)
Scarless skin regeneration remains one of the most ambitious goals in regenerative medicine. Unlike fibrotic healing, which results in excessive collagen accumulation and functional impairment, true regeneration restores both the structural integrity and physiological function of skin, including the reconstitution of hair follicles and other appendages. Retinoids, a broad class of natural and synthetic vitamin A derivatives, have attracted increasing attention for their potential to modulate wound repair at multiple levels. These compounds regulate a diverse array of biological processes, including epidermal differentiation, fibroblast activation, immune response, and extracellular matrix remodeling. This review provides a comprehensive overview of how retinoids coordinate cellular and molecular events across key skin compartments during healing. Retinoids have been reported to suppress TGF-β1/Smad signaling, inhibit myofibroblast differentiation, and restore matrix homeostasis, thereby exerting anti-fibrotic effects. In addition, retinoid-based therapies enhance re-epithelialization, stimulate angiogenesis, and promote dermal regeneration when incorporated into advanced biomaterial systems. Recent studies further demonstrate that retinoids can support skin appendage regeneration, including de novo hair follicle formation, a hallmark of functional repair typically absent in adult wounds. In view of converging evidence from developmental biology, stem cell research, and regenerative engineering, retinoids present a promising pharmacological strategy in reduced-scarring healing and functional skin regeneration.